COVID-19 vaccine intercountry distribution inequality and its underlying factors: a combined concentration index analysis and multiple linear regression analysis - Abu El Kheir-Mataria, Wafa; Khadr, Zeinab; El Fawal, Hassan; Chun, Sungsoo (Frontiers in Public Health, 2024)
The inequitable access to the COVID-19 vaccine among countries is one of the significant health equity concerns at the global level. Economic power, political power, political stability, and health system strength were recognized as underlying factors for inequities in COVID-19 vaccine distribution. This study aims to estimate the inequality in the distribution of COVID-19 vaccines among countries according to these factors and to determine which factors are related to the COVID-19 vaccine distribution among countries. Concentration Index (CI) analysis was used to determine inequalities in the distribution of COVID-19 vaccines among countries by four separate variables (GDP/capita, Political Stability (PS), World Power Index (WPI), and Universal Health Coverage (UHC). Multiple linear regression analysis was used to estimate the relationship between the distribution of the COVID-19 vaccines and each of the four precedent-independent variables. Two COVID-19 vaccine distribution variables were used to ensure the reliability of the results. Inequity in the distribution of COVID-19 vaccines among countries according to the countries' GDP/capita, PS, WPI, and UHC for both vaccine courses delivered as a proportion of the country population (VPP) and Total vaccinations per hundred people within a given population (TVH) are present. However, the multiple linear regression analysis showed no significant relationship between COVID-19 vaccine distribution and the countries' GDP per capita. The regression analysis proved that TVH and VPP are significantly related to the three other factors: WPI, PS, and UHC. UHC appears to be the most influential factor related to the distribution and accessibility of the COVID-19 vaccine.